2023
DOI: 10.3390/antiox12020248
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Antioxidant, Antidiabetic, Antibacterial, Cytoprotective Potential and Metabolite Profile of Two Endophytic Penicillium spp.

Abstract: The current study assessed the metabolite abundance, alpha (α)-amylase and α-glucosidase inhibitory, antioxidant, and antibacterial activity of the ethyl acetate extract (EAE) of endophytic Penicillium lanosum (PL) and Penicillium radiatolobatum (PR). A higher extract yield was found in EAE-PR with a total phenolic content of 119.87 ± 3.74 mg of GAE/g DW and a total flavonoid content of 16.26 ± 1.95 mg of QE/g DW. The EAE-PR inhibited α-amylase and scavenged ABTS+ radicals with a half-maximal inhibitory concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The DPPH radical was estimated as described earlier [22]. Nine concentrations (7.8, 15.6, 31.3, 62.5, 125, 250, 500, 1000, 2000 µg/mL) of D. arborea and B. ferruginea and ascorbic acid were used.…”
Section: Dpph and Abts + Free Radical Scavenging Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The DPPH radical was estimated as described earlier [22]. Nine concentrations (7.8, 15.6, 31.3, 62.5, 125, 250, 500, 1000, 2000 µg/mL) of D. arborea and B. ferruginea and ascorbic acid were used.…”
Section: Dpph and Abts + Free Radical Scavenging Activity Assaymentioning
confidence: 99%
“…The TF content of each extract was quanti ed as described earlier [22]. Brie y, 100 µL of each extract (at 1 mg/mL) was mixed with distilled water (250 µL) and ethanol (150 µL; 95%).…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant properties of natural compounds are largely associated with their electron-donating and free radical neutralizing ability, thus contributing to their reducing powers. Therefore, determining the reducing power of natural compounds is commonly linked to their antioxidant capacity, making the ferric reducing assay a reliable approach for determining and quantifying the antioxidant activity of antioxidants [23,42]. The ferric reducing potential of IPS-1, IPS-2, and AA was positively correlated with the concentration dosage (Figure 6c).…”
Section: Ferric-reducing Antioxidant Powermentioning
confidence: 99%
“…Among them, Penicillium is an important Genus comprising more than 400 identified species. Further, biomolecules of Penicillium species, such as alcohol, penicillin, peptides, and organic acids, are promising in agriculture, food, and medicinal industrial applications [22,23]. Some earlier works reported that IPS and EPS were isolated from Penicillium sp., and determined their promising biological activities [11,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, drought stress poses a signi cant impact on the delicate water balance in cocoa plants, resulting in unfavorable growth, development, and yield outcomes (Oyekale, 2021). A prominent outcome of drought conditions is the production of reactive oxygen species (ROS) in the plant's cellular structure (Jin et al, 2023;Naveen et al, 2023). These ROS molecules are known to possess a strong reactivity, capable of in icting harm to cellular constituents, including chlorophyll molecules (Sharma et al, 2023;Gupta and Pandey, 2022).…”
Section: Introductionmentioning
confidence: 99%